Sosialisasi Penyaluran BBM Subsidi Jenis Solar Ke Petugas SPBU Cangkring Di Demak - Herri Wijaya (Abdimas Mandalika, 2023)
Abstract: Starting from a lot of news about modified trucks for transporting diesel fuel on the Demak pantura route. So an Socialization Activity was held for the Distribution of Subsidized Diesel Fuel to Cangkring Gas Station Officers in Demak Regency. This PKM socialization must be intensified to gas station officers so that they provide information about which vehicles are entitled to consume diesel fuel, do not commit unlawful violations such as the incident from the gas station described above and know a lot about the criminal provisions of Chapter XI article 53 which reads that everyone who processes, transport and storage. With various stages of implementation such as observation accompanied by interviews, making preparations, the implementation process is in the form of briefings and providing a statement of commitment not to distribute Solar BBM to those who are not entitled. This activity yielded 100% useful knowledge to gas station operators regarding the distribution of subsidized diesel fuel and provided everyone's willingness not to sell or distribute to those who are not entitled to it, as evidenced by a stamped statement.and then need to be aware that vehicles buying diesel fuel are still relatively high, so it needs very strict supervision from gas station operators so that they are always on target in the distribution.Abstrak: Berawal dari banyak berita tentang truck modifikasi untuk pengangkut BBM jenis solar di jalur pantura Demak. Maka diadakanlah Kegiatan Sosialisasi Penyaluran BBM Subsidi Jenis Solar Ke Petugas SPBU Cangkring Di Kabupaten Demak. Sosialisasi PKM ini harus digencarkan kepada petugas SPBU supaya memberikan informasi perihal Kendaraan apa saja yang berhak mengkonsumsi solar, tidak melakukan pelanggaran yang melawan hukum seperti kejadian dari SPBU yang dijelaskan diatas dan banyak tahu tentang ketentuan Pidana BAB XI pasal 53 berbunyi setiap orang yang melakukan pengolahan, pengangkutan dan penyimpanan. Dengan berbagai tahap pelaksanaan seperti Observasi disertai wawancara, melakukan persiapan, proses pelaksanaan berupa briefing dan memberikan surat pernyataan komitmen tidak menyalurkan BBM Solar kepada yang tidak berhak. Kegiatan ini menghasilkan 100% ilmu bermanfaat kepada Operator SPBU tentang penyaluran BBM subsidi jenis solar dan memberikan kesediaan semuanya untuk tidak menjual atau menyalurkan kepada mereka yang tidak berhak dengan dibuktikan dengan surat pernyataan bermaterai. Dan perlu waspada bahwa kendaraan yang membeli solar masih tergolong tinggi jadi perlu pengawasan yang begitu ketat dari Operator SPBU supaya selalu tepat sasaran dalam penyalurannya tersebut.